Do anthropometric characteristics and physical capacities of highly trained junior badminton players differ according to age and sex? - Winata, B.; Brochhagen, J.; Apriantono, T.; Hoppe, M. W. (Frontiers in Sports and Active Living, 2025)
Introduction: In badminton, anthropometric characteristics and physical capacities are essential to meet playing demands across ages and sexes. The objective of this study was to investigate age- and sex-related differences in anthropometric characteristics and physical capacities among highly trained junior badminton players, focusing on differences between (i) under (U) 13, U15, and U17 age groups, and (ii) sexes within each age group.